Closed-End Fund Discounts with Informed Ownership Differential - Grullon, Gustavo; Albert Wang, F. (Journal of Financial Intermediation, 2001)
We develop a multiasset trading model to examine the closed-end fund discount. The model shows that the discount can arise if the quality of private information in the underlying assets is sufficiently better than in the fund. The model also indicates that a discount (premium) can arise if the excessive volatility of the fund dominates (is dominated by) the fund's diversification benefit. Moreover, the model predicts a negative relation between the discount and the institutional ownership differential, as arbitrageurs prefer funds with large discounts. Using a sample of U.S. equity closed-end funds, we test these predictions and find supporting evidence. Journal of Economic Literature Classification Numbers: D82, G10, G12, G14.